2014
DOI: 10.1007/s10072-014-1651-6
|View full text |Cite
|
Sign up to set email alerts
|

APOE and LRPAP1 gene polymorphism and risk of Parkinson’s disease

Abstract: Epidemiologic findings suggest that lipids and alteration in lipid metabolizing protein/gene may contribute to the development of neurodegenerative disorders. The aim of the current study was to determine the serum lipid levels and genetic variation in two lipid metabolizing genes, low-density lipoprotein receptor-related protein-associated protein (LRPAP1) and apolipoprotein E (APOE) gene in Parkinson's disease (PD). Based on well-defined inclusion and exclusion criteria, this study included 70 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
2
24
1
1
Order By: Relevance
“…The large sample size in the current study also permitted estimation of associations with different statin types (lipophilic vs hydrophilic). In contrast to prior studies 17,18 with much smaller sample sizes, we found that lipophilic statins were associated with highest PD risk. Conversely, a significant association was not found for nonstatin cholesterollowering agents, but the less frequent use of these drugs left this aspect of the study underpowered.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The large sample size in the current study also permitted estimation of associations with different statin types (lipophilic vs hydrophilic). In contrast to prior studies 17,18 with much smaller sample sizes, we found that lipophilic statins were associated with highest PD risk. Conversely, a significant association was not found for nonstatin cholesterollowering agents, but the less frequent use of these drugs left this aspect of the study underpowered.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite this uncertainty, 14,18 there has been a prevailing sentiment to use statins as neuroprotective agents [19][20][21] ; indeed simvastatin (a lipophilic statin) is in a current clinical trial. 19 It is, therefore, timely to evaluate carefully the relationship of statins and PD risk.…”
mentioning
confidence: 99%
“…PTPN14 is a member of the protein tyrosine phosphatase family, and it has been reported to be a regulator of lymphatic function and choanal development (Au et al, 2010;Mendola et al, 2013). LRPAP1 interacts with the low density lipoprotein receptor-related protein, and reports have shown that this gene was associated with myopia and Parkinson's disease (Khan et al, 2016;Singh et al, 2014). Up to now, most of the 13 mRNA have not been studied in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…There are fascinating mechanisms that may be relevant, for example, a large clinical study provided evidence that lipids and lipoproteins may affect dopamine neuron–specific signaling cascades . Other studies show that cholesterol recycling may be linked to PD, and related genes are associated with increased PD risk or are affected in animal models of PD or PD itself …”
Section: Contributions From the Basic Sciencesmentioning
confidence: 99%
“…114 There are fascinating mechanisms that may be relevant, for example, a large clinical study provided evidence that lipids and lipoproteins may affect dopamine neuron-specific signaling cascades. 115 Other studies show that cholesterol recycling may be linked to PD, 109,110,114 and related genes are associated with increased PD risk 116 or are affected in animal models of PD 117 or PD itself. 118 Despite the literature linking serum/plasma total and LDL cholesterol to PD, 26,27,30,40,47,[96][97][98][99][100][101][102] the cause of the association is not known and further complicated by the compartmentalization of the brain and peripheral cholesterol.…”
Section: Glucose Lipid and Cholesterol Metabolismmentioning
confidence: 99%